Analisis penerapan bisnis model canvas (studi pada UKM di kota malang) - Siwi Dyah Ratnasari; Sunarto Sunarto (Fakultas Ekonomi Universitas Kadiri, 2021)
One of the ways that companies can compete and develop is by creating new, different strategies. The business model acts as a model that describes how a company moves to make a profit. The Business Model Canvas (BMC) is considered effective because it explains thoroughly both in terms of marketing, human resources, finance, to the value or product offered. This study aims to analyze and formulate the development of the Canvas business model in Lapar Pool UKM. This research uses descriptive qualitative research methods. Data collection methods using interview techniques. The results show that there is a picture of 9 elements in the current business model canvas and the formulation of a business model development in the form of a picture of 9 elements of the new business model canvas. The new business model canvas is expected to cover weaknesses in the previous business model so as to minimize risks or threats to the company, which consists of: 1) Customer Segments, 2) Value Propositions, 3) Channels, 4) Customer Relationships, 5) Revenue Streams, 6) Key Resources, 7) Key Activities, 8) Key Partnerships, 9) Cost Structures.The research implication is that the Business Model Canvas is formed from 9 elements that are interrelated with each other, therefore it is important to understand every aspect covers business functions, activities and operations in order to create adjustments for business progress